Key Factors that Led to the Derailment of the Ajaokuta Steel Project - Okpighe, Sunday Okerekene; Alajemba, Charles C. (International Journal For Research In Mechanical & Civil Engineering, 2016)
A review into the factors that militated against the success of the Ajaokuta Steel Project in Nigeria is reported . The Acts setting up the Iron and Steel Industry, the Chronological development in this Sector and the research publications of scholars in this Sector were reviewed. Several factors as identified by these scholars as negating the success of the Ajaokuta Project were noted. Against the background of the body of knowledge inherent and available in these reports, the Key Factors that led to the derailment of the Ajaokuta Steel Project were identified.